STRATEGI INTERNALISASI NILAI-NILAI KARAKTER DI MTs NEGERI 1 HULU SUNGAI SELATAN - Islamiati, Marliana; Jazuli, Sulaiman (IAIN Bone, 2024)
AbstractThe phenomenon that is often seen related to character is the real evidence that there is a contradiction between the behavior of educated people and the behavior that should be displayed. The actions of educated people even show bad morals. The morals they display are not by the basic objectives of national education. This means that there is a contradiction between the results and the goals that national education aims to achieve. This type of research uses field research, located at MTs Negeri 1 Hulu Sungai Selatan, the subjects in this study were the head of the madrasah and educators, instruments and data collection techniques using observation, interviews, and documentation techniques, and data analysis techniques in this study using qualitative descriptive analysis. The three strategies carried out by schools are caring attitudes that are developed not limited to the classroom, familiarizing good morals in the school environment, and synergizing with parents and the community. The strategies carried out by educators are educators as role models, creating moral communities in the classroom, implementing moral discipline, and encouraging moral reflection. The character values instilled are the characteristics of environmental care, hard work, religion, creativity, national spirit, respect for achievement, and honest character.So, it can be concluded that there are four character internalization strategies carried out by educators, and three strategies carried out by schools. The internalized character values are the characteristics of environment Awareness, hard work, religious, creative, patriotic, appreciate to the achievement, and honest.